Using PCR for detection of cutaneous leishmaniasis in Baghdad - Kamil, Marwa M.; Ali, Hayder Z. (Iraqi Journal of Science, 2022)
Cutaneous Leishmaniasis (CL) is an endemic disease and one of the major health problems in Iraq. Leishmania tropica is known as the causative agent of Cutaneous Leishmaniasis in Baghdad.The classical serological methods of diagnosing leishmaniasis is a poor sensitivity especially for the sub genus and time consuming Here we have investigated two primer pairs, one specific for Leishmania as genus and the primer specific for the species of L. tropica to be detected by polymerase chain reaction (PCR).Samples were collected from (AL-karama Teaching Hospital) and whole genomic DNA was extracted from axenic promastigotes.The extracted DNA was amplified by PCRwith two KDNA primer pairs, for genus specific (13A/13B) and (Lmj4/Uni21) to identify the specific species of cutaneous leishmaniasis. Amplified PCR products then run on gel electrophoresis and two visible bands of the two primers were seen, 120 and 800 bp, respectively. Our results indicate that the PCR technique is sensitive and specific for the detection and differentiation of cutaneous leishmaniasis agents and can be recommended to applied in hospitals and research centers.